"Ειδικοί" διανοούμενοι κι θύλακες χειραφέτησης στο Μεσοπόλεμο. Μεταρρυθμιστές γεωπόνοι και μηχανικοί στην ύπαιθρο και το άστυ - ΣΩΤΗΡΟΠΟΥΛΟΣ, Δ. Π.; ΠΑΝΑΓΙΩΤΟΠΟΥΛΟΣ, Δ. (Μνήμων, 2011)
The mid-war period had been characterized by transformations of great importance regarding the Greek social and economic field. During the first two decades of the 20th century, due to different causes (geopolitical upheavals in the region, inflow of refugees, changes in the political system etc) several aspects of the social structure had been developed in a way that led to a more positive point of view towards new professional groups that had been emerged, mainly technicians such as agriculturists, architects, civil engineers or economists. In Foucault’s terms, these scientists and scholars who remain cloistered in their field, are considered to be “specific” intellectuals, in opposition to intellectuals par excellence, that is the universal intellectuals who used to play the role of a universal consciousness and a counterpoise to the service of the State or Capital. Their new “truth”, is not outside the systems of power and because of that “truth” is to be understood here as a system of ordered procedures for the production, regulation, distribution, circulation and operation of statements, creating a “regime” of truth. However, as Pierre Bourdieu put it, the authority of the specialist on a certain field (agriculture or architecture, in this case) gives him/her the right to intervene publicly in order to indicate the most appropriate path to the rise of productivity or the refinement of the civic way of life – which ends to be a political intervention. These particular professional groups proved to be the pioneers in the project of reorganizing and rearranging the structure of country’s rural and civic space, a political project, the leading management of which had been held by the Venizelist party and its modernization program. As a whole, it proved to be a liberal and effective project, at least in the beginning. Eventually, this evolution would also be accompanied by the rise of a modern culture of emancipation as far the mid-war Greek society concerned. It remains an interesting issue to search for this new mentality of emancipation in the forthcoming years of massive social mobilization, especially during the resistance and civil war period. It ended up, however, raising struggles against other powerful and competitive elite groups, i.e. lawyers, but the most important was that this tendency to larger autonomy raised fears from the part of the political power and the state apparatus who tried to control and patronize the specific intellectuals.